ZANTEDESCHIA AETHIOPICA (L.) SPRENG.: A REVIEW OF ITS MEDICINAL USES, PHYTOCHEMISTRY, AND BIOLOGICAL ACTIVITIES: ETHNOPHARMACOLOGY OF ZANTEDESCHIA AETHIOPICA - MAROYI, ALFRED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Zantedeschia aethiopica is an evergreen monocotyledonous herb widely used as herbal medicine and ornamental plant. The current study is aimed at reviewing the medicinal uses, phytochemistry, and biological activities of Z. aethiopica. Information on biological activities, medicinal uses, and phytochemistry of Z. aethiopica was gathered from several internet sources which included Scopus, Google Scholar, Elsevier, Science Direct, Web of Science, PubMed, SciFinder, and BMC. Additional information on these aspects was sourced from pre-electronic sources such as journal articles, scientific reports, theses, books, and book chapters obtained from the University Library. The current study revealed that Z. aethiopica is mainly used as herbal medicine for boils, burns, gout, inflammation, insect bites, rheumatism, sores, and wounds. Phytochemical and pharmacological studies showed that Z. aethiopica extracts and compounds isolated from the species have antibacterial, antifungal, antioxidant, antihistaminic, antialgal, antithrombotic, and anticoagulant activities. This research showed that Z. aethiopica is an integral part of the traditional pharmacopeia in several countries where the species is indigenous or naturalized, but there is the lack of alignment between the known medicinal applications, phytochemistry, and biological activities of the species. Therefore, future research should focus on evaluating the chemical and pharmacological properties of Z. aethiopica extracts and compounds associated with the species.